Penerapan Strategi Perubahan Pemasaran Melalui Media Digital Pada Bulan Ramadhan di Kala Pandemi Covid-19 - Minta Ito Lubis; Nuri Aslami (Universitas Muhammadiyah Enrekang, 2022)
This study aims to describe how the phenomenon of the Covid-19 Pandemic and the month of Ramadan that occurred in Indonesia can disrupt the stability of the economy in Indonesia, especially for MSME actors so that a marketing change strategy through digital media is needed to maintain business and develop business through the use of digital media. These changes can provide insight into the behavior of product marketers. The marketing strategy in this year's Ramadan is not enough if it only involves a plan that is in accordance with market conditions during the Covid-19 pandemic, but also needs to implement a good customer focus. The application of customer focus can be said to be a must in a product marketing effort. As a marketer, it is very important to pay attention to the quality of service. Considering that maximum service has major implications for customer satisfaction and ultimately has implications for the performance of the business being carried out, paying attention to the wishes of the community as a customer focus to produce a comprehensive strategy that is in accordance with the characteristics of the intended customer. If this can be combined well, product marketing in the month of Ramadan can be successful even though it is carried out in the midst of many limitations due to the Covid-19 pandemic. The results of this study provide various strategies that business actors can do, including selling by e-commerce, doing digital marketing, improving product and service quality, and establishing good relationships with consumers or establishing customer marketing relationships.